2020
DOI: 10.2147/ndt.s262510
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of Chronotypes and Sleep Disturbance with Perceived Job Stressors and Stress Response: A Covariance Structure Analysis</p>

Abstract: Background: Chronotype, which is a person's circadian characteristics throughout a day, greatly influences a person's lifestyle, health, and sleep pattern; however, the association between job stress and chronotype remains unknown to date. Therefore, in this study, we analyzed the effects of chronotype on the job stress response, and the mediating effects of sleep disturbance using path analysis. Methods: A cross-sectional survey was conducted on 535 adult volunteers (239 men and 296 women; average age, 41.2 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Furthermore, sleep disturbance and work-related stress affect presenteeism [ 53 ]. A recent study suggests that improving sleep disturbance may reduce a worker’s stress response [ 54 ]. Regarding interventions, internet-based cognitive behavioral therapy for insomnia may be a cost effective strategy [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sleep disturbance and work-related stress affect presenteeism [ 53 ]. A recent study suggests that improving sleep disturbance may reduce a worker’s stress response [ 54 ]. Regarding interventions, internet-based cognitive behavioral therapy for insomnia may be a cost effective strategy [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed as a cross-sectional survey using selfadministered questionnaires. The data of the participants have been used in previous studies investigating the associations between job stress and sleep rhythm (Miyama et al, 2020) or resilience (Sameshima et al, 2020). First, the effect size of physical activity on mental health was conservatively estimated as "small to medium" (Cohen's d = 0.2 to 0.5).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…A systematic review has supported the proposition that work can be beneficial for an employee's mental health, particularly if good-quality supervision is provided and workplace conditions are favorable (Modini et al, 2016 ). Additionally, as another important personal factor, sleep status is strongly associated with psychological and physical stress reactions (Åkerstedt et al, 2002 ; Miyama et al, 2020 ) and presenteeism (Furuichi et al, 2020 ; Ishibashi and Shimura, 2020 ) in the workplace, and may be affected by the COVID-19 pandemic (Rajkumar, 2020 ; Wang et al, 2020 ). Some studies have assessed the associations between the COVID-19 pandemic and mental health, the working environment (Galanti et al, 2021 ), and home conflicts (Freisthler et al, 2021 ), and the advantages and disadvantages of remote work, and one study reported the positive effects of remote work on stress reactions during the pandemic (Darouei and Pluut, 2021 ).…”
Section: Introductionmentioning
confidence: 99%